Verificação das demoras obstétricas e outros fatores associados à ocorrência do desfecho near miss materno - Lima, Sâmua Kelen Mendes de (2018)
The main objective of this study was to verify the influence of obstetric delays and other tors with an occurrence of the outcome near maternal miss. Epidemiological study, cross sectional, with quantitative data analysis. Cases of technological issues were identified, as well as the application of theoretical references of the Three Delays Model. The study popula tion was composed of puerperal women admitted to the high risk puerperium and the Mater nal Unit of the Assis Chateaubriand Maternity School (MEAC), during the period from May to October 2017, totaling 185 women. The instrument of data collection according to identifi cation data, sociodemographic data, obstetric data, pre-existing maternal conditions, potential ly life-threatening conditions, near miss criteria, newborn data and investigation of delays. The data were compiled and analyzed through the program Statistical Package for Social Sci ences (SPSS) version 24.0 and software R 3.3. The predominant age group in the study was between 18 and 35 years of age, the majority of the women were from Fortaleza, which has a split plot, of brown breed, and that has more than nine years of study. Regarding the obstetric profile, almost all the women performed prenatal care, most of OMSm were in another insti tution, with more than five visits. Most women have had more than two pregnancies. As for the way of delivery, a cesarean section prevailed before labor began and almost half of the games performed before 36 weeks of gestation. Regarding maternal conditions pre-existing at gestation, there was a predominance of arterial hypertension, obesity and heart disease. Re garding the potentially life-threatening conditions, hypertensive complications predominated, being a main clinic grave and pre-eclampsia. Of the other complications, there was a predom inance of thrombocytopenia and hemorrhagic complications. As variables Postpartum haem orrhage, grave Pre-eclampsia, HELLP syndrome, eclampsia, thrombocytopenia, cardiomyo pathy and obstetric delays increased a chance of developing NMM. Regarding the occurrence of delays, there was a prevalence of phase 1 delay, which was referred to the woman and her family, due to the phase 3 delay, which refers to the health services and, finally, the phase 2 delay, which is related with the route to the health service. A statistical association between an occurrence of delays and maternal outcomes of MMG and ICU admission was verified. The results were followed in conjunction with the "live" birth condition and the neonatal out come of hospital discharge. Also, a prematurity was related to the stillbirth condition and ne onatal death. And the development of NMM was related to an occurrence of late neonatal death. In view of the findings, it is recommended that as causes of delays and better monitors at all levels of attention, with the reduction of perinatal complications, such as severe mater nal morbidity and maternal near miss.